2021
DOI: 10.1111/jzs.12509
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic biogeography of Tobago's marooned relics: The case study of a fossorial snake (Squamata, Dipsadidae)

Abstract: The islands of Trinidad and Tobago form a southern extension of the Lesser Antilles.Unlike the continental island of Trinidad, the more northerly Tobago formed as an older oceanic island volcanic arc. Their reptile biodiversity reflects colonization events from the South American mainland through land bridge connections at times of glacial maxima. Most of Tobago's herpetofauna has colonized through stepping-stone events from Trinidad. However, the enigmatic presence of a rare and poorly known fossorial snake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The time tree (Figure 5) suggests that the presence of P. turpinorum in Tobago is likely the result of a vicariant event roughly at the time of the detachment of Trinidad from northern Venezuela circa 4–5 Ma, followed by a stepping‐stone colonization event to Tobago with extinctions of intermediate populations in Trinidad thereafter. A different scenario implies a direct colonization event from the mainland to Tobago, as is the case for other species such as the glass frog Hyalinobatrachium orientalis , which is only present in Tobago and northern Venezuela (Jowers et al, 2015) or the Hallowell's ground snake A. fuliginosus , which is present in Tobago and central‐western Venezuela (Jowers et al, 2021). Under this last scenario, Tobago would have been positioned several kilometers to the west of its current position and it could had been easier to colonize directly from the mainland, explaining the absence of the species in Trinidad, as has already been proposed for another anuran (Jowers et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The time tree (Figure 5) suggests that the presence of P. turpinorum in Tobago is likely the result of a vicariant event roughly at the time of the detachment of Trinidad from northern Venezuela circa 4–5 Ma, followed by a stepping‐stone colonization event to Tobago with extinctions of intermediate populations in Trinidad thereafter. A different scenario implies a direct colonization event from the mainland to Tobago, as is the case for other species such as the glass frog Hyalinobatrachium orientalis , which is only present in Tobago and northern Venezuela (Jowers et al, 2015) or the Hallowell's ground snake A. fuliginosus , which is present in Tobago and central‐western Venezuela (Jowers et al, 2021). Under this last scenario, Tobago would have been positioned several kilometers to the west of its current position and it could had been easier to colonize directly from the mainland, explaining the absence of the species in Trinidad, as has already been proposed for another anuran (Jowers et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Until the work reported here, no other study had found that some mainland Pristimantis species are closely related to some insular species. Four scenarios support the presence of closely related species between northern Venezuela and Tobago: (1) when Tobago's position was much further west of its current position (Jowers et al, 2015), shallow marine depths (<50 m) in the region and sea‐level falls during the Pliocene (Miller et al, 2005) would have facilitated land‐bridge connections between northern Venezuela and Tobago (Jowers et al, 2015); (2) through stepping‐stone connection of several Pliocene islands that once existed between Tobago and the mainland and Trinidad, and all of the islands were connected by very shallow and likely emergent coastal systems (Jowers et al, 2021; Samlal, 2016); (3) over‐water dispersal with frogs rafting on vegetation, possibly from river mouths or an estuary such as the Orinoco Delta (Camargo et al, 2006; Yanek et al, 2006); and (4) a stepping‐stone colonization from Trinidad with subsequent extinctions locally, which remains more unlikely due to the much larger area of suitable habitat present in Trinidad's Northern Range. Further sampling and sequencing of other loci are required to run accurate phylogenetic interpretations and models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations